Penerapan Regresi Linier Berganda dalam Menilai Hubungan Antar Variabel dalam Penelitian Kuantitatif - Aflah, Fadli Ramadhanul; Risnawati, Risnawati; Hamdani, M. Fikri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the application of multiple linear regression in analyzing the relationship between several independent variables with one dependent variable in the context of quantitative research. The approach used is a literature study with a qualitative descriptive method, which examines the latest literature on multiple linear regression. Data were collected from various sources such as books, national journal articles, and relevant scientific publications in the last four years. This study discusses the basic concept of multiple linear regression, its calculation formula, and the classical assumption test that must be met so that the regression model can be used validly in prediction and analysis. The analysis in this study refers to the multiple linear regression procedure using the Ordinary Least Squares method to obtain optimal parameter estimates. The results of the study indicate that multiple linear regression is an effective method in explaining the simultaneous relationship between variables, and is able to describe the direction, strength, and level of significance of the influence of each independent variable on the dependent variable. With a deep understanding of the technical and theoretical aspects of multiple linear regression, researchers can build strong and reliable prediction models, especially in the fields of education, social, and economics.